THE MANAGEMENT OF ZAKAT IN INDONESIA: A HISTORICAL REVIEW - Kamal Ibrahim; Sepky Mardian (Kopertais Wilayah I DKI Jakarta dan Banten, 2018)
The Management of zakat in Indonesia has been going on since Islam entered Indonesia till today. This study aims to explain how the management of zakat in Indonesia is patterned on Islamic principles. The study uses a descriptive method with historical approach. The study of the history of Islam and Indonesia became the basis for determining the findings, on the pattern of management of zakat in Indonesia. The findings showed that the pattern of management of zakat in the beginning at the time of the entry of Islam in the colonial period, had a huge role in the society. This pattern became one of models of management of zakat